Effects of vitamin C supplementation on blood pressure and hypertension control in response to ambient temperature changes in patients with essential hypertension. (4th July 2019) - Yuan, Xiaojie; Li, Xiaochun; Ji, Zhaohua; Xiao, Jing; Zhang, Lei; Zhang, Weilu; Su, Haixiao; Kaliannan, Kanakaraju; Long, Yong; Shao, Zhongjun
ABSTRACT: Evidence for blood pressure-lowering effects of vitamin C (VC) supplementation in clinical trials is inconsistent and limited studies have examined the effect of VC supplementation on hypertension (HTN) control. In this study, eligible patients were cluster assigned to receive 300 mg VC per day or nothing for 6 months. During the 6-month follow-up period, a questionnaire survey was obtained and standardized blood pressure measurements were performed on all subjects. Oral administration of VC significantly decreased the diastolic blood pressure and pulse pressure with a significant increase in HTN control. After adjusting for confounding variables, treatment with VC was associated with 0.5 risk reduction of uncontrolled HTN in subjects received anti-hypertensive medications, whereas lower indoor and outdoor and ground temperature were significantly associated with an increased risk of uncontrolled HTN in all patients. Our results warrant further studies investigating the mechanisms underlying the association between VC and HTN control.